New-Onset Atrial Fibrillation in COVID-19 Infection: A Case Report and Review of Literature - Shah, Deesha; Umar, Zaryab; Ilyas, Usman; Nso, Nso; Zirkiyeva, Milana; Rizzo, Vincent (Curēus (Palo Alto, CA), 2022)
Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, many cases of arrhythmias have been reported in patients with COVID-19 infection. We present the case of a 66-year-old female with no known cardiovascular history who presented with worsening shortness of breath and productive cough and tested positive for COVID-19 infection in the ED. The patient had a recent hospitalization for COVID-19 infection during which she was treated with dexamethasone and remdesivir therapy and her course remained uncomplicated at that time. Following this, she developed worsening shortness of breath at home for which she presented to the ED. During this hospitalization, she was treated with dexamethasone, remdesivir, and supplemental oxygen. On day six of hospitalization, the patient became tachycardic and had palpitations. Cardiac monitor and EKG showed evidence of new-onset atrial fibrillation (NOAF). Initially patient received metoprolol and diltiazem, both of which failed to achieve adequate rate control. Following this, the patient was started on carvedilol 30 mg every six hours, which attained good rate control. Her CHA2DS2-VASc (congestive heart failure, hypertension, age ≥75 (doubled), diabetes, stroke (doubled), vascular disease, age 65 to 74, and sex category) score was 4 for which she was started on apixaban 5mg twice daily. The patient was discharged on the same medications. Despite increasing reported incidences of NOAF in COVID-19 infection, only little is known about the optimal management strategies and possible etiopathology. The aim of our review is to highlight the possible mechanisms triggering atrial fibrillation in COVID-19 infection and go over the management strategies while reviewing the available literature.